395 AMBULATORY CARE SENSITIVE CONDITIONS AND RACIAL DISPARITIES IN PEDIATRIC INPATIENT ADMISSION SEVERITY, LENGTH OF STAY, CHARGES AND MORTALITY. (1st January 2005) - Teufel, R. J.; Simpson, K. N.; Darden, P. M.
Abstract : Background: Ambulatory care sensitive conditions (ACSC) are potentially preventable reasons for hospital admission. African-American (AA) and Hispanic children have less access to care than non-minorities. Objectives: To examine pediatric admission severity, hospital utilization, and mortality measure in children with ACSC for evidence of racial disparity in care. Methods: Data from the 2000 Healthcare Cost and Utilization Project Kids' Inpatient Database (HCUP KIDs), a national inpatient discharge survey database, were used to examine hospital admissions for children age 0-18 years admitted for an ACSC first diagnosis. The ACSC diagnoses examined were asthma, pneumonia, upper airway conditions, seizures, cellulitis, and dehydration. Hospital utilization was measured as length of stay and charges. Admission severity is defined as emergent, urgent, elective, or other. Race/ethnicity was defined as Hispanic and non-Hispanic white, AA, and other. The analyses accounted for the complex sample design and are reported as means and 95% confidence interval. Results: ACSC diagnoses account for 26.15% of pediatric inpatient admissions. AA children are more likely to be admitted emergently than Hispanic or white children (61% vs 37%, 38%; p < .01). But missing data for admission type was more common for Hispanic vs AA or white children (33% vs 10%, 10%; p < .01). LOS increased from white (mean 2.60; 95% CI 2.53-2.66) to AA (2.75; 2.68-2.83) to Hispanic (3.02; 2.90-3.13). Charges increased from white (5, 714; 5, 394-6, 034) to AA (6, 636; 6, 179-7, 094) to Hispanic (8, 567; 7, 891-9, 242). The mortality for ACSC admissions was not different between groups but overall was rare at .09%. Conclusions: Children of different race/ethnicities admitted for ACSC conditions appear to be different on admission and have different hospital utilization once admitted. Examination of racial disparities of inpatient care must carefully control for these admission differences that are likely effects of differences in access to care. Existing data are of concern because missing data appear to also be different by race/ethnicity.